Hubungan antara Ekspresi Gambar Orang dan Faktor-Faktor Kepribadian 16PF - Reni Nurhayati; Agung Santoso (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2018)
This study aims to determine how the dimensions of Draw A Person test (DAP) is able to uncover traits from the 16 PF test (The Sixteen Personality Factor Questionnaire). Data from 200 subject who filled the DAP and 16 PF tests were processed and analyzed using exploratory factor analysis and regression. From the analysis of factor analysis to people's image expression data, we obtained 8 sets of factors, namely Factor I - VIII from DAP. From the regression test between Factor 16 PF and the factor image test of the person, it was found several Factors 16 PF which can be used to predict some expressions of people's images. These factors include Factor Q3 which is able to predict Factor VII and Factor Q4 that is able to predict Factor I.